MENINGKATKAN KEPUTUSAN PEMBELIAN MELALUI PROMOSI BERKELANJUTAN PADA SEPATU LOKAL GEOFF MAX DI GEOFF MAX STORE KEMANG - Eva Nur Fitasari; Parlagutan Silitonga (Human Capital Development, 2022)
This study aims to prove the influence of product quality, and brand image on purchasing decisions through promotions at Geoff Max Store Kemang. The population in this study were customers who bought shoes at Geoff Max Store Kemang. The sampling technique used accidental sampling of 132 respondents. The data collection method uses questionnaires that are distributed to respondents, with quantitative methods. Meanwhile, hypothesis testing structural equation model with the help of SmartPLS 3.0. The results of this study brand image and sustainable promotion directly have a positive and significant effect on purchasing decisions, brand image indirectly has a positive and significant effect on customer decisions through sustainable promotion. However, product quality does not have a significant effect on purchasing decisions and product quality indirectly does not have a significant effect on purchasing decisions through sustainable promotion. Keywords : Product Quality, Brand Image, Sustainable Promotion, and Purchasing Decision